Caputring professionalism in pre-service education: professionalism tool development and implementation. - Russell, Barbara; Owen, Mary Anne; Leibach, Elizabeth; Meaders, Eric; Stone, Rebecca B.; Kraj, Barbara (Clinical Laboratory Science)
Recognizing that all health professions educational programs seek to graduate students possessing characteristics embodying the nebulous concept of professionalism, educators in four imaging and radiation science programs and a clinical laboratory science program collaborated to create a measurement tool for professionalism in pre-service education. The Student Professional Behavior Evaluation Tool and the process for its development and implementation are described.